A new Campylocentrum (Vandeae; Epidendroideae; Orchidaceae) from submontane Atlantic Forest of northeastern Brazil - Pessoa, Edlley; Alves, Marccus (Phytotaxa, 2015)
A new species of Campylocentrum with reduced stems, small conduplicate leaves and long inflorescences is described from submontane Atlantic forest of Pernambuco state, northeastern Brazil. It is related to C. hirtellum, but differs by having a pedicellate ovary and base of the perianth both slightly papillate, smaller sepals, mid-lobe of the lip less than three times longer than the lateral lobes, lip 5-nerved, spur slightly longer than the pedicellate ovary and a glabrous capsule. It is illustrated and its affinities with allied species are also discussed.